Addressing climate change through climate action - Tosun, Jale (Climate action, 2022)
This editorial introduces the journal Climate Action to its audience and defines its aims and scope. It first calls for the need to understand climate action as the choices and behavior of international organizations, governments, civil society, businesses, and individuals. Next, it discusses both the facilitators and impacts of climate action. The editorial concludes with a research agenda for climate action to be studied from a transdisciplinary perspective with practitioners for triggering widespread societal transformation.
Gesehen am 12.07.2023